Textural improvement of salt-reduced Alaska pollack (Theragra chalcogramma) roe product by CaCl2. (15th December 2016) - Chen, Chaoping; Okazaki, Emiko; Osako, Kazufumi
Highlights: A novel method for preparing salt-reduced Alaska pollack roe was developed. The effect of NaCl on the Alaska pollack roe during salting was clarified. CaCl2 showed a positive impact on the texture of salted Alaska pollack roe. CaCl2 concentration were optimized for maximum TGase activity during salting. Abstract: Salt-reduced Alaska pollack roe benefits public health by decreasing NaCl intake; however, it has a poor texture with low breaking strength. This study addresses the feasibility of NaCl reduction in salted roe products, with focusing on the improvement of breaking strength using CaCl2 . Salted roe products were prepared by immersing Alaska pollack roe in either NaCl solutions (3.5, 7.0, 15.0, 20.0, and 25.0%) or 7.0% NaCl solutions with added CaCl2 (0.0, 0.5, 1.0, 2.0, and 3.0%). Breaking strength, moisture and salt contents, eggshell protein composition of the salted roe products, as well as total endogenous transglutaminase (TGase) activity in various NaCl and CaCl2 concentrations were analyzed. CaCl2 addition enhanced eggshell protein crosslinking and breaking strength of the salt-reduced roe products. An acyl transfer reaction catalyzed by calcium-dependent TGase may be responsible for the eggshell protein crosslinking and improved texture. Thus, we successfully developed a salt-reduced Alaska roe product using CaCl2 .